Investigation of the Death Anxiety and Meaning in Life Levels among Middle-Aged Adults - Müge Yukay Yüksel; Ferit Güneş; Ceren Akdağ (Spiritual Psychology and Counseling)
Life and death constitute a whole, and these concepts become increasingly important in the evaluation of life among middleaged adults. Therefore, this study investigated the correlation between individual levels of death anxiety and meaning in life in terms of certain variables such as gender, age, educational status, marital status, perceived level of devoutness, and witness to death. The sample consisted of 185 individuals (82 males, 103 females; aged 25–55 years) living in Istanbul, Turkey. The data was collected by using a Personal Information Form, the Death Anxiety Scale, and the Meaning in Life Questionnaire. The findings showed that, as the death anxiety and meaning in life subscale levels increased, the meaning in life levels decreased. In addition, it was found that death anxiety does not differ according to the following variables: age (25–35 and 35–55 years), educational status, marital status, perceived religious belief, and living with someone. The results also indicated that women tend to experience more death anxiety than men, and that individuals who witnessed the death of a close person generally feel more death anxiety than those who did not.